Affine and toric arrangements - Richard Ehrenborg; Margaret Readdy; Michael Slone (Discrete Mathematics & Theoretical Computer Science, 2008)
We extend the Billera―Ehrenborg―Readdy map between the intersection lattice and face lattice of a central hyperplane arrangement to affine and toric hyperplane arrangements. For toric arrangements, we also generalize Zaslavsky's fundamental results on the number of regions.